Ribosome Synthesis in Rhodopseudomonas capsulata Cells Growing In Continuous and Intermittent Light - Din, George A. (J Bacteriol, 1969)
The ribosome content was markedly reduced when illumination (at 28 C) was repeatedly interrupted; an opposite trend was observed with continuous light as the temperature was decreased.